Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/1361-6382/abc666
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-local Casimir energy and vacuum buoyancy in a weak gravitational field

Abstract: Casimir energy in presence of a weak gravitational field is discussed taking into account the issues related to energy and its conservation in a curved background. It is well-known that there are inherent difficulties in defining energy in general relativity, essentially due to its non-localizability. Using the concept of quasi-local mass and energy, it is shown that it is possible to attribute a Tolman mass to a massless scalar field confined to a Casimir cavity. Such non-local mass coincides—as expected—with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…It is worth also point out the contribution of the subject concerning the relationship between Casimir effect and traversable wormholes to the raise of new insights with respect to the issue if gravity in fact modifies the vacuum energy (and, vice-versa, if this latter gravitates), at least in weak field regime. This topic is actually object of discussion [9,10] and some proposals concerning observational investigations, as the Archimedes experiment [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth also point out the contribution of the subject concerning the relationship between Casimir effect and traversable wormholes to the raise of new insights with respect to the issue if gravity in fact modifies the vacuum energy (and, vice-versa, if this latter gravitates), at least in weak field regime. This topic is actually object of discussion [9,10] and some proposals concerning observational investigations, as the Archimedes experiment [11].…”
Section: Introductionmentioning
confidence: 99%
“…( 32), and the deflection angle of light becomes Eq. (33). Moreover, we analyzed the special case ω = 3, in which the deflection angle of massive particles with finite distances becomes Eq.…”
Section: Discussionmentioning
confidence: 99%
“…This theme has raised new insights about the issue if gravity effectively modifies the vacuum energy (and, vice-versa, if this latter gravitates), at least in the weak-field regime. This is presently an object of discussion in the literature [33][34][35] and of proposes of observational investigations, as in the Archimedes vacuum weight experiment [36]. Concerning wormholes, the study of Casimir plates in the orbit of wormholes can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the study of the relationship between the Casimir effect and traversable wormholes can lead to the arising of novel insights with respect to the issue if gravity in fact influences the vacuum energy (and, vice-versa, if this latter gravitates), at least in a weak field regime. This topic is actually object of discussion [13][14][15] as well as of projects for observational investigations, as in the Archimedes experiment [16].…”
Section: Introductionmentioning
confidence: 99%